THE M G QUEUE BUSY PERIOD LENGTH EXPONENTIAL BEHAVIOR FOR PARTICULAR SERVICE TIMES DISTRIBUTIONS COLLECTION - Ferreira, Manuel Alberto (Acta Scientiae et Intellectus, 2024)
The aim of this work is to look for exponential behavior conditions for the queue busy period length distribution, in the case at which a particular service time’s collection is considered.